2014
DOI: 10.2478/s13545-014-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Larval development and settlement of the barnacle Amphibalanus amphitrite from the Red Sea: Influence of the nauplii hatching season

Abstract: Barnacle Amphibalanus amphitrite adults were collected from the Jeddah coast of the Red Sea during different seasons. The nauplii released by adults in autumn, winter, spring and summer were reared under laboratory conditions to know the larval development duration and settlement in relation to the hatching season. The nauplii reared during winter (11 days) and autumn (13 days) took longer to reach the cypris stage compared to nauplii reared in summer (6 days) and spring (7 days). The most successful settlemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It is important to note that the reproductive cycles of most of the taxa observed in this study are not known in Saudi Arabian Red Sea region. However, recent studies by Al-Aidaroos & Satheesh (2014) reported the pronounced seasonality (active breeding in spring and summer) in reproductive cycle of barnacles in the central Red Sea region. We assume that other species may also follow a seasonal reproductive cycle and that thi could be a possible reason for observed seasonal fluctuations.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that the reproductive cycles of most of the taxa observed in this study are not known in Saudi Arabian Red Sea region. However, recent studies by Al-Aidaroos & Satheesh (2014) reported the pronounced seasonality (active breeding in spring and summer) in reproductive cycle of barnacles in the central Red Sea region. We assume that other species may also follow a seasonal reproductive cycle and that thi could be a possible reason for observed seasonal fluctuations.…”
Section: Discussionmentioning
confidence: 98%
“…Effects of Acute and Chronic Exposure of PMMA Nanoplastics on Barnacle Larvae Development. The growth of barnacle larvae consists of three stages, 47,48 and the duration in which the larvae remain in each of these stages is mainly dependent on temperature and nutrient availability. 49 In order to understand the impact of nanoplastics on different life stages, investigations on the distribution of nanoplastics inside barnacle larvae were conducted at three-time points: stage III nauplii (2 days old), cyprid (5 days old), and juvenile (7 days old).…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…Exopolymers isolated from biofilm bacterial strains were tested against the larvae of barnacle A. amphitrite . Like other marine invertebrates, A. amphitrite has greater ecological significance among rocky intertidal habitats and it is also commonly used as a model organism in antifouling studies 28–30 . Specifically, the following questions were addressed in this study: (1) do the exopolymers induce settlement and metamorphosis of A. amphitrite larvae?…”
Section: Introductionmentioning
confidence: 99%